Composition of cladoceran dormant stages in intermittent ponds with different hydroperiod lengths. Issue 6 (6th September 2017) - Stenert, Cristina; Wüsth, Regiane; Pires, Mateus Marques; Freiry, Raquel Fontoura; Nielsen, Daryl; Maltchik, Leonardo
Abstract: Dormancy is an adaptive mechanism found in cladoceran species to tolerate hydrologic fluctuations in temporary habitats. However, the effects of hydroperiod length on invertebrate community structure remain not fully understood. In this study, we conducted an experiment to assess changes in community structure of dormant stages of cladoceran species among ponds with different hydroperiods. Dry sediment samples were collected from intermittent ponds in southern Brazil, posteriorly assigned to three hydroperiod categories (long, medium and short). We tested for differences in the richness and composition of emerging cladoceran species along this hydroperiod gradient. Nine species emerged over the experiment, and cladoceran community structure changed among hydroperiods. Cladoceran richness was higher in medium‐ than in short‐ and long‐hydroperiod ponds. In addition, the composition of cladoceran species changed significantly between short‐ and long‐hydroperiod ponds. Our results indicated that changes in hydroperiod of intermittent ponds influenced the dormant stages of Cladocera, an important result regarding future predicted changes in hydric regime of freshwater ecosystems due to human‐induced climate change. We propose that desiccation‐resistant cladoceran species are likely to predominate and that richness of egg banks tends to be higher in ponds that hold water for periods shorter than 1 year.